2018
DOI: 10.25066/agrotec.v39i1.37088
|View full text |Cite
|
Sign up to set email alerts
|

Desempenho operacional e econômico do terraceamento de pequenas propriedades com arados de discos

Abstract: O terraceamento com arados de discos ainda é prática comum em pequenas propriedades rurais, munidas de implementos e tratores de menor porte. O objetivo do trabalho foi avaliar o desempenho operacional e econômico de diferentes modelos de arados de discos comumente usados na construção de terraços em pequenas propriedades rurais. O experimento foi realizado com arados de discos e tratores em três pequenas propriedades rurais nos municípios de Botucatu-SP e Avaré-SP. O delineamento experimental utilizado foi o … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 3 publications
1
2
0
Order By: Relevance
“…The lowest Operating Cost in the construction of the terraces was obtained by the drag plow, followed by the reversible plow and the fixed plow. The values obtained by the reversible and fixed plows corroborate the results found by Correia et al (2018) who concluded that, regardless of the number of discs, the reversible plows provided greater operational efficiency and effective field capacity.…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…The lowest Operating Cost in the construction of the terraces was obtained by the drag plow, followed by the reversible plow and the fixed plow. The values obtained by the reversible and fixed plows corroborate the results found by Correia et al (2018) who concluded that, regardless of the number of discs, the reversible plows provided greater operational efficiency and effective field capacity.…”
Section: Resultssupporting
confidence: 87%
“…The construction effective capacity of each terrace was determined according to Equation 10, adapted from Correia et al (2018). Then, the Operational Cost was obtained, according to Correia et al (2018), using Equation 11:…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation